2017
DOI: 10.1523/jneurosci.2170-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of NMDA Receptor- and Voltage-Gated L-Type Calcium Channel-Dependent Hippocampal LTP Critically Rely on Proteolysis That Is Mediated by Distinct Metalloproteinases

Abstract: Long-term potentiation (LTP) is widely perceived as a memory substrate and in the hippocampal CA3-CA1 pathway, distinct forms of LTP depend on NMDA receptors (nmdaLTP) or L-type voltage-gated calcium channels (vdccLTP). LTP is also known to be effectively regulated by extracellular proteolysis that is mediated by various enzymes. Herein, we investigated whether in mice hippocampal slices these distinct forms of LTP are specifically regulated by different metalloproteinases (MMPs). We found that MMP-3 inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 61 publications
5
66
1
Order By: Relevance
“…Glial cells express critical components of the PNN, and expression of components is regulated by factors including neuronal activity (Howell and Gottschall, ; Matthews et al, ; McRae et al, ; Song and Dityatev, ). In addition, several PNN cleaving enzymes are expressed by neurons and glia (Brzdak, Wlodarczyk, Mozrzymas, & Wojtowicz, ; Deb and Gottschall, ; Dubey et al, ; Janusz et al, ; Pollock, Everest, Brown, & Poulter, ; Szklarczyk, Lapinska, Rylski, McKay, & Kaczmarek, ; Wiera et al, ; Yong, Krekoski, Forsyth, Bell, & Edwards, ). Soluble and transmembrane matrix metalloproteinases have been particularly well studied for their potential to disrupt PNN integrity, and their expression and/or activity is can be dramatically altered by physiological or pathological neuronal activity (Conant et al, ; Meighan et al, ; Nagy et al, ), disease states and select therapeutics (Pollock et al, ; Szklarczyk et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Glial cells express critical components of the PNN, and expression of components is regulated by factors including neuronal activity (Howell and Gottschall, ; Matthews et al, ; McRae et al, ; Song and Dityatev, ). In addition, several PNN cleaving enzymes are expressed by neurons and glia (Brzdak, Wlodarczyk, Mozrzymas, & Wojtowicz, ; Deb and Gottschall, ; Dubey et al, ; Janusz et al, ; Pollock, Everest, Brown, & Poulter, ; Szklarczyk, Lapinska, Rylski, McKay, & Kaczmarek, ; Wiera et al, ; Yong, Krekoski, Forsyth, Bell, & Edwards, ). Soluble and transmembrane matrix metalloproteinases have been particularly well studied for their potential to disrupt PNN integrity, and their expression and/or activity is can be dramatically altered by physiological or pathological neuronal activity (Conant et al, ; Meighan et al, ; Nagy et al, ), disease states and select therapeutics (Pollock et al, ; Szklarczyk et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Glial cells express critical components of the PNN, and expression of components is regulated by factors including neuronal activity (Howell and Gottschall, 2012;Matthews et al, 2002;McRae et al, 2007;Song and Dityatev, 2017). In addition, several PNN cleaving enzymes are expressed by neurons and glia (Brzdak et al, 2017;Deb and Gottschall, 1996;Dubey et al, 2017;Janusz et al, 2013;Pollock et al, 2014;Szklarczyk et al, 2002;Wiera et al, 2017;Yong et al, 1998). Soluble and transmembrane matrix metalloproteinases have been particularly well studied for their potential to disrupt PNN integrity, and their expression and/or activity is can be dramatically altered by physiological or pathological neuronal activity (Conant et al, 2010;Meighan et al, 2006;Nagy et al, 2006), disease states and select therapeutics (Szklarczyk et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Thus, not surprisingly, MMPs are precisely controlled. In the CNS, MMPs are expressed and secreted both by neurons and glial cells 13 but their activity in normal conditions is low. The level of MMP activity significantly increases only in specific time windows, for example, during the induction of synaptic plasticity or repairing processes.…”
Section: Matrix Metalloproteinases and Mmp-3mentioning
confidence: 99%
“…Moreover, recent studies have confirmed that MMP-3 activity is indeed crucial in regulating vdcc-dependent form of LTP in hippocampus, but not for nmdaLTP (that is regulated, e.g., by MMP-9). 13 Nevertheless, there is also some evidence that MMP-3 can affect NMDA receptors. In cultured spinal cord neurons, chronic NMDAR overstimulation leads to an increase in MMP-3 activity which, in turn, cleaves GluN1 subunit of NMDA receptor to constrain calcium influx and prevent neuron apoptosis.…”
Section: Matrix Metalloproteinase-3 In Synaptic Plasticity Learning mentioning
confidence: 99%
See 1 more Smart Citation